Recognition of prior learning in workplaces: exploring managerial practice by the means of a heuristic conceptual framework - Assinger, Philipp [Verfasser] (My University, 2023)
„The focus of Recognition of Prior Learning (RPL) on assessment and credentials has ambivalent implications regarding research on workplace RPL. This article presents and empirically tests a heuristic conceptual framework to support the analysis of workplace RPL and its relation to learning at work. RPL is defined as a practice of workplace pedagogy with two modes of recognition attributed a performance, a developmental, and an occupational orientation. The framework is applied to analyse data from an interview-based study with managers in Austrian wood-processing companies. The analysis reveals a strong orientation towards performance, adaptive learning, and immediate use of skills. A strength-based view of staff development and awareness of the importance of support positively influence occupationally relevant and developmental learning. When recognition is a part of everyday management practice and workplace participation, there are even greater opportunities for developmental learning. This article offers conceptual perspectives and empirical evidence to researchers and practitioners. The implications for practice suggest an intensification of support for managers to help them appreciate the potential benefits of RPL. For future research, it is indicated among others to further develop, strengthen, and empirically validate the heuristic conceptual framework.“ (author‘s abstract; BIBB-Doku)

Der Artikel beschäftigt sich mit der Frage, wie Lernleistungen und Kompetenzen am Arbeitsplatz anerkannt werden. Diese Frage wird am Beispiel von Geschäftsführer:innen von Betrieben der steirischen Holzwirtschaft bearbeitet. Daneben wird auch ein Rahmenmodell der Anerkennung am Arbeitsplatz entworfen, das zur Analyse betrieblicher Bildung anwendbar ist. (BIBB-Doku)
Keywords: L 2.1.3 Erfahrungslernen; L 2.1.1 Informelles Lernen; S 2.2.4.4 Anerkennung non-formaler Qualifikationen; 370; Erfahrungsorientiertes Lernen; Erfahrungswissen; Informelles Lernen; Lernen am Arbeitsplatz; Anerkennung; Adaptives Lernen; Holzindustrie; Interview; Österreich